A Study on the perception of Boys and Girls in secondary level from Tea Garden areas of Titabor, Assam in regards to their School Environment - Swapna Sikha Das (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This paper is inclined towards Study on the perception of Boys and Girls in secondary level from Tea Garden areas of Titabor ,Assam in regards to their School Environment. It gives us an understanding of students towards multidimensional learning environment of the school. It tries to assess how school environment impacts school behavior and perception of the students , how teacher behavior impacts school environment , how different dimensions of school environment shape the dynamics of students' perception and adjustment in relation to school environment and relation to school effectiveness. School Environment Inventory developed and standardized by Dr. Kurana Shankar Mishra was administered on 98 boys and 98 girls studying at secondary level. The result of the study showed significant different between boys and girls about school environment in various dimensions.